(untitled) (UNIZIK Journal of STM Education, 2024)
The main purpose of this study was to determine the influence of personality types and gender on students’ achievement in quantitative analysis. For this descriptive survey research, two research questions and two hypotheses were generated. Using two well-validated instruments (Students’ Achievement Test in Quantitative Analysis (SATQA), and Student’s Personality Type Questionnaire (SPTQ), the data was collected from 600 chemistry students from 5 randomly selected schools in Akure South Local Government, Ondo State. This was analyzed using frequency counts, mean, percentage, Analysis of Variance (ANOVA), and t-test. The results are that most of the respondents (72.5%) had low achievement in quantitative analysis in chemistry. Also, regarding students’ personality types, agreeableness was ranked highest based on the mean score, followed by openness, conscientiousness, extraversion, and neuroticism, implying that agreeableness is the most predominant personality. It was found that there was no significant difference in students’ achievement in quantitative analysis based on personality type (F (4, 595) = 0.76; p>0.05). There was also no significant difference in male and female students’ achievement in quantitative analysis in senior schools’ chemistry (t = 0.07; p>0.05). We concluded that both personality types and gender had no impact on students’ achievement in Quantitative Analysis in chemistry. However, it is recommended that teachers make efforts to create chemistry learning environments with consideration for the differences relating to students’ personality types and gender.